Digital detox, the need of the hour: a cross-sectional study on psychometric evaluation of college students using smart phones - Ainsy Goldlin TJ; Prakash M; Ezhil Ramya J; Meenakshi B (Al Ameen Medical College, 2022)
Aim: The aim of the study was to analyse the pattern of mobile usage and its impact on behaviour among college students. Methods: A cross-sectional, semi-structured questionnaire based study was conducted among 275 students of various colleges of Tamil Nadu after obtaining IEC clearance. Quantitative data is expressed as mean ± standard deviation and compared by independent sample t test or ANOVA. Qualitative data is expressed in percentages. Results: Out of the 275 study participants, 140 were from medical college and 135 were from non- medical colleges. Around 42.8% participants were using mobile phones for 3-6 hours per day and 58% were using social media more frequently in a day. The estimated mean of the behavioural analysis score with the social media usage and mobile phone usage revealed that the mean score increased if the usage of social media or mobile increased (p < 0.001). Conclusion: The pattern of mobile phone use among the college students reported in this study appears to have some behavioural influence on them. This has to be recognized at an earlier stage and measures must be taken to reduce it.